Increased Plasma Levels of Soluble CD27 among HIV/HCV Co-infected and HIV/HCV/GBV-C Triply Infected Subjects - Najafi, Alireza; Haji Mollahoseini, Mostafa; Samiee, Shahram; Amini Kafi-Abad, Sedigheh; Memarnejadian, Arash (Archives of Advances in Biosciences, 2013)
CD27 is a biomarker associated with both T-cells and B-cells activation .Plasma soluble CD27 (sCD27) was identified as a marker of disease outcome in Human Immunodeficiency Virus (HIV) infection .Testing of plasma sCD27 represents a good tool to monitor the change of immune activation during HIV infection.We sought to analyses role of Hepatitis C Virus (HCV) and also GB Virus type C (GBV-C) co-infections on HIV-related immune activation, through measuring sCD27 plasma levels.Blood samples from a total of 86 patients with HIV infection were taken. Plasmas were analyzed for HCV using serologic test and GBV-C by reverse transcriptase polymerase chain reaction (RT-PCR). CD4+ and CD8+T-cell counts were evaluated by CD3/CD4+ and CD3/CD8+ double staining of whole blood followed by flow cytometric analysis .Then Cross-sectional comparison of sCD27 plasma levels was carried out among patients : HIV (n=20), HIV/ GBV-C (n=14), HIV/ (HCV) (n=26) and HIV/HCV/GBV-C (n=26).Plasma level of sCD27 was higher in HIV/HCV/GBV-C patients as compared to HIV mono-infected patients (p= 0.006) and based on results there was significant differences in the plasma levels of sCD27 between HIV-infected individuals with and without HCV coinfection (P=0.017) and also correlation between sCD27 and percent of CD4+T-cells was in highest level among HIV/HCV co-infected patients group [r= -0.59 (p=0.001)]. High levels of sCD27 among HIV/HCV patients argues in favor of sCD27 plasma level determination for monitoring of clinical features among HIV/HCV coinfected patients.